THE INFLUENCE OF GEOGRAPHIC FACTORS ON ECONOMIC DEVELOPMENT - MARKOSIAN, Ashot; PETROSIAN, Makar (CENTRAL ASIA AND THE CAUCASUS, 2011)
There are many studies that show how a country’s production capacity greatly depends on its geographical location. Most economic production indices are characterized by a simple regressive dependence in production volume density (GDP per 1 sq. km) on geographic variables (average annual temperature, average annual amount of precipitation, altitude above sea level, ruggedness of landscape, soil categories, access to the sea, etc.).Does this mean that geographic factors are determining the fate of a country’s development? If so, to what extent? If not, what measures should be taken to ensure long-term economic growth? We will try to shed light on these and other issues in this article.